The first record of Epistylis niagarae on Astacus leptodactylus in a crayfish rearing unit, cip - Harlio?lu, Muzaffer Mustafa (My University, 1999)
In this study, the presence of the ectocommensal Epistylis niagarae on the carapace, abdomen, walking legs, uropod, telson, antennae and antennulae of crayfish was observed.
Keywords: Astacus leptodactylus; Ectocommensal; Epistylis niagarae